Abundance, primary production rates and net calcification rates of Tridacna maxima giant clams at two reefs in the Central Red Sea - Rossbach, Susann; Saderne, Vincent; Anton, Andrea; Duarte, Carlos Manuel (Supplement to: Rossbach, S et al. (2019): Light-dependent calcification in Red Sea giant clam Tridacna maxima. Biogeosciences, 16(13), 2635-2650, https://doi.org/10.5194/bg-16-2635-2019, 2019)
Abundance data of Tridacna maxima giant clams at 6 different depths (0.5, 1.5, 3, 5 , 8 and 11m) at two reefs (Station 1 - 22.303833 N, 39.048278 E) and Station 2 - 20.753764 N, 39.442561 E ) in the Central Red Sea. Primary production in Tridacna maxima giant clams was assessed during the three different incident light incubations (561, 959, and 1061 μmol quanta m-2 s-1). Oxygen (μmol L-1) content in the incubation chambers was automatically logged (miniDOT, Precision Measurement Engineering, Inc., USA) in 15 min intervals over the 3 h incubation period. Net photosynthesis (NPP) was calculated from the variation of oxygen concentration over time and normalized for clam mantle surface area (μmol O2 cm-2 h-1). Dark respiration rates (R), also given in μmol O2 cm-2 h-1, were used to calculate gross primary production (GPP) as: GPP = NPP +R. Net calcification rates of the giant clam Tridacna maxima were determined under 7 different light levels (1061,959, 561, 530, 358, 244, and 197 μmol quanta m-2 s-1) and in the dark. At the start, after 3 h and after 6 h of each incubation, seawater was sampled from each experimental aquaria in gas tight 100mL borosilicate bottles (Schott Duran, Germany) and poisoned with mercury chloride, following Dickson et al. (2011). Each sample was analysed for TA by open-cell titration with an AS-ALK2 titrator (Apollo SciTech,USA) using certified seawater reference material (Andrew Dickson, Scripps Institution of Oceanography). During the incubations at moderate light levels (530, 358, 244,and 197 μmol quanta m-2 s-1), additional samples for dissolved inorganic carbon (DIC) were analysed using an ASC3 infrared DIC analyser (Apollo SciTech, USA). Further components of the carbonate system were calculated with R package Seacarb (Lavigne and Gattuso, 2013) using first and second carbonate system dissociation constants of Millero (2010) as well as the dissociations of HF and HSO-4 (Dickson, 1990; Dickson and Goyet, 1994), respectively. Net calcification (G in μmol CaCO3 h-1) was estimated from changes in total alkalinity (TA) using the alkalinity anomaly technique (Smith and Key, 1975), where delta TA is the variation of TA during the time (t ) of the incubations and the factor 2 accounts for a decrease in TA by two equivalents per CaCO3 precipitated (Zeebe and Wolf-Gladrow, 2001). Calcification rates were expressed relative to either mantle surface area (cm2) or tissue dry mass (g). For mantle surface area, the power relationship between standard length in centimetres (L) and mantle area (cm2) (Jantzen et al., 2008) was used to calculate the mantle surface in cm2. For tissue dry mass (DM in gram) of 5 clams, all clams were dissected and their biomass was determined subsequently to the incubation experiment. Clams were opened by cutting the adductor muscle with a scalpel, and the mantle and other tissues were separated from the shells and dried at 60 Degree Celsius for 24 to 48 h to determine tissue DM to the nearest 0.01 g.